The Influence of Social Media, Price, and Venue on Concert Ticket Purchasing Decisions at The Motikdong.Com Website - Wahyudi Wahyudi (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This study examines whether social media, price, and venue influence the Decision to Purchase Concert Tickets. This research is quantitative. The sample in this study is concert audience customers who have purchased concert tickets on the Motikdong.com website. The population in this study were Motikdong Indonesia Instagram account followers and ticket buyers who had bought directly on the motikdong.com website. The sample in this study was 335 respondents who were determined using the Slovin formula. The results of data analysis using SPSS 23 prove that there is a positive and significant influence both partially and simultaneously between Social media, price, and Venue variables on Purchase Decisions on concert tickets on the motikdong.com website with a contribution (R2) of 77.2% and a value F count, which is 373,982 > F table, which is 2,631, which means that social media, price, and venue variables influence the decision to purchase tickets on the motikdong.com website. Partially, each independent variable significantly influences the dependent variable, where the venue variable has a dominant value compared to other independent variables, with a value of 93.4.